Representational deficit or processing effect? An electrophysiological study of noun-noun compound processing by very advanced L2 speakers of English - De Cat, Cecile; Klepousniotou, Ekaterini; Baayen, R. Harald (Frontiers in Psychology, 2015)
The processing of English noun-noun compounds (NNCs) was investigated to identify the extent and nature of differences between the performance of native speakers of English and advanced Spanish and German non-native speakers of English. The study sought to establish whether the word order of the equivalent structure in the non-native speakers' mothertongue (L1) had an influence on their processing of NNCs in their second language (L2), and whether this influence was due to differences in grammatical representation (i.e. incomplete acquisition of the relevant structure) or processing effects. Two mask-primed lexical decision experiments were conducted in which compounds were presented with their constituent nouns in licit versus reversed order. The first experiment used a speeded lexical decision task with reaction time registration, and the second a delayed lexical decision task with EEG registration. There were no significant group differences in accuracy in the licit word order condition, suggesting that the grammatical representation had been fully acquired by the non-native speakers. However, the Spanish speakers made slightly more errors with the reversed order and had longer response times, suggesting an L1 interference effect (as the reverse order matches the licit word order in Spanish). The EEG data, analysed with generalized additive mixed models, further supported this hypothesis. The EEG waveform of the non-native speakers was characterized by a slightly later onset N400 in the reversed constituent order. Compound frequency predicted the amplitude of the EEG signal for the licit word order for native speakers, but for the reversed constituent order for Spanish speakers - the licit order in their L1- supporting the hypothesis that Spanish speakers are affected by interferences from their L1.